2020
DOI: 10.1136/rmdopen-2019-001030
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus is not a risk factor for osteoarthritis

Abstract: BackgroundAssociation between diabetes mellitus (DM) and risk of osteoarthritis (OA) can be confounded by body mass index (BMI), a strong risk factor for both conditions. We evaluate the association between DM or hyperglycaemia with OA using systematic review and meta-analysis.MethodsWe searched PubMed and Web of Science databases in English for studies that gave information on the association between DM and OA. Two meta-analysis models were conducted to address: (1) risk of DM comparing subjects with and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 40 publications
(80 reference statements)
2
25
0
3
Order By: Relevance
“…While some studies have reported associations of diabetes and dyslipidemia with knee OA, 8,9,12,34,35 others have found no associations. 36,37 Two meta-analyses reported associations of diabetes with OA even when controlling for BMI 8,9 while a more recent meta-analysis found no association. 36 In a meta-analysis of 48 studies, Baudart et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies have reported associations of diabetes and dyslipidemia with knee OA, 8,9,12,34,35 others have found no associations. 36,37 Two meta-analyses reported associations of diabetes with OA even when controlling for BMI 8,9 while a more recent meta-analysis found no association. 36 In a meta-analysis of 48 studies, Baudart et al .…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Two meta-analyses reported associations of diabetes with OA even when controlling for BMI 8,9 while a more recent meta-analysis found no association. 36 In a meta-analysis of 48 studies, Baudart et al . demonstrated an association of dyslipidemia with OA.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent meta-analysis with nine studies showed that even though pooled results of case-control and cross-sectional studies suggested a strong relationship between dyslipidemia and KOA, this relationship was not validated by meta-analysis of only cohort studies [ 34 ]. Similarly, an updated meta-analysis with 31 studies failed to show that diabetes is an independent risk factor for KOA, after incorporating BMI into the analysis [ 35 ]. Taken together, these results indicated that MetS was not an independent risk factor for overall KOA in general population after adjustment of confounding factors including BMI.…”
Section: Discussionmentioning
confidence: 99%
“…ЦД і остеоартрит (ОА) є поширеними захворюваннями, пов'язаними зі спільними для них факторами ризику й ускладненнями. Хоча дуже часто можна зустріти суперечливі висновки стосовно ролі різних факторів ризику в розвитку ураження суглобів у хворих на ЦД [6]. Крім того, основні дослідження стосувалися колінних і кульшових суглобів [1,9,10], рідше -суглобів кисті [11,12].…”
Section: вступunclassified
“…Інші фактори, такі як вік, етнічна приналежність, стать, індекс маси тіла (ІМТ), артеріальна гіпертензія, нейропатія і дисліпідемія, які впливають як на ЦД, так і на ОА, не були повністю вивчені [13,14]. Слід відзначити, що донедавна ЦД не вважався чинником ризику розвитку ОА, якщо не зважати на роль ЦД у розвитку артропатій, які об'єднують не лише ОА, але й інші форми ураження суглобів (тугорухливість суглобів, артрити тощо) [6,15]. Роль ожиріння в розвитку ОА не викликала сумнівів, при цьому відзначалося саме підвищення навантаження на несучі суглоби, зокрема колінні; при цьому зв'язку надмірної маси тіла із розвитком ОА не виявляли [16,17].…”
Section: вступunclassified